Homozygous mutation of MTPAP causes cellular radiosensitivity and persistent DNA double-strand breaks - Martin, N T (Nature Publishing Group, 2014)
The study of rare human syndromes characterized by radiosensitivity has been instrumental in identifying novel proteins and pathways involved in DNA damage responses to ionizing radiation. In the present study, a mutation in mitochondrial poly-A-polymerase (MTPAP), not previously recognized for its role in the DNA damage response, was identified by exome sequencing and subsequently associated with cellular radiosensitivity. Cell lines derived from two patients with the homozygous MTPAP missense mutation were radiosensitive, and this radiosensitivity could be abrogated by transfection of wild-type mtPAP cDNA into mtPAP-deficient cell lines. Further analysis of the cellular phenotype revealed delayed DNA repair, increased levels of DNA double-strand breaks, increased reactive oxygen species (ROS), and increased cell death after irradiation (IR). Pre-IR treatment of cells with the potent anti-oxidants, α-lipoic acid and n-acetylcysteine, was sufficient to abrogate the DNA repair and clonogenic survival defects. Our results firmly establish that mutation of the MTPAP gene results in a cellular phenotype of increased DNA damage, reduced repair kinetics, increased cell death by apoptosis, and reduced clonogenic survival after exposure to ionizing radiation, suggesting a pathogenesis that involves the disruption of ROS homeostasis.